How to Get a PhD: A Handbook for Students and Their Supervisors - Phillips, Estelle M.; Pugh, Derek S. (Berkshire Open University Press, 2005)
A welcome revision to what has always been a popular book amongst intending PhD students; certainly an essential for all careers libraries!...Order your copy of the book today, and watch your students queue to consult it!" - Phoenix"Phillips and Pugh's book has, since its original publication in 1987, become the undisputed bible for doctoral students...To say that this book is a goldmine of hints, sound advice and carefully researched observations and lessons is an understatement." - Nursing Times --This text refers to an out of print or unavailable edition of this title.